Internationalization, Technological Change and the Theory of the Firm. - De Liso, Nicola (Routledge Studies in Global Competition, v. 50, 2010)
Focuses on three areas, each of which is central to economic theorising: firms' organisation and behavior, technological change and the process of globalisation. This book looks at various questions surrounding firms' organisation, including why we can observe ordered paths of production, and whether proximity between firms matters.